Analysis Coldplay Jakarta Concert: Fear Of Missing Out (Fomo) Phenomenon On Tiktok Platform - Ahmad Khoiril Imam; Avissa Abli Umayyah; Mukarto Siswoyo; Aghnia Dian Lestari (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The era of globalization and advances in information technology have changed people's consumptive behavior in entertainment and music. Music is an important component in everyday life as a medium of self-expression. Research (Qadri, 2008),  (Asriyani, 2019) , and Raharjo (2018) highlights the importance of music concerts in maintaining cultural heritage and enculturation, as well as strengthening audience bonds with modern and popular attitudes while maintaining authenticity. The objective of this research is to identify and analyze how the phenomenon of Fear of Missing Out (FoMO) related to the Coldplay concert in Jakarta is presented and disseminated through the TikTok platform. Additionally, this study aims to explore the role of TikTok as a social media platform in triggering and amplifying feelings of FoMO among users in this context. Furthermore, the research seeks to assess the impact of TikTok content about the Coldplay concert on user behavior, identify the demographic groups most vulnerable to FoMO through TikTok usage, and determine the influencing factors. This theory, developed by Katz and Gurevitch, was used from a concert-goer perspective, specifically the phenomenon of TikTok fear of missing out on the Coldplay concert in Jakarta. This research recorded details and collected data from five informants aged 20-29 who are fans of music concerts and Coldplay, using purposive sampling method. The interviews revealed that FoMO (Fear of Missing Out) plays an important role in individuals' motivation to follow music trends and entertainment events. FoMO negatively impacts mental and emotional health, as well as finances, and leading to consumptive behavior.